The Mental Attitude of Jesus at Bethany: John 11. 33, 38 - Story, Cullen I. K. (New Testament studies, 1991)
Both secular and sacred texts indicate that the verb έμβρ. and its congeners may convey, at times, a more violent expression of ‘wrath’ such as is found in the description of the persecutors of Christians in Gaul (Eusebius) or in the meaning of ‘curse’ (cf. Hermias on Empedocles) or ‘exasperation’ (Aquila in Jer 10.10) or even as a substitute for όργή (Symmachus and Theodotion on Ezek 21.36). At other times, έμβρ. and its congeners shade into the meaning of έπειλή ‘threat’ (Basil on Ps 37) or even of έπιτιμάω ‘rebuke’ (cf. Symmachus on Isa 17.13).